2020
DOI: 10.1111/ntwe.12175
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of social media for German work councils representing qualified employees—the case of a German car manufacturer

Abstract: The world of work is undergoing huge changes as a result of digitalisation. Part of this transformation process involves a growing demand for skilled employees-a section of the workforce that appears increasingly less reliant on the representative services provided by works councils. In the following article, we consider works council's use of ICT tools to re-engage with skilled employees, noting that current institutional and cultural contingencies appear to hinder its employment of ICT tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The findings demonstrate a series of distinctive ways in which AI can potentially be used to increase union power resources (Ibid., 10–12). Similar to Staples and Whittall (2021), the authors conclude that harnessing the potential of AI, however, is overwhelmingly dependent upon the mediation of the industrial relations context and the ways in which these technologies are designed (Ibid., 13).…”
Section: Contributions To the Special Issuementioning
confidence: 77%
See 2 more Smart Citations
“…The findings demonstrate a series of distinctive ways in which AI can potentially be used to increase union power resources (Ibid., 10–12). Similar to Staples and Whittall (2021), the authors conclude that harnessing the potential of AI, however, is overwhelmingly dependent upon the mediation of the industrial relations context and the ways in which these technologies are designed (Ibid., 13).…”
Section: Contributions To the Special Issuementioning
confidence: 77%
“…The first article by Staples and Whittall (2021) investigates the potential of social media to enhance the representation and democratic participation of skilled employees in the German car manufacturing sector. On the one hand, digitalisation is creating a growing demand for skilled employees who appear to have become less reliant on the representative services of work councils 11 due partly to greater use of ICTs within the workplace (Ibid., 2).…”
Section: Contributions To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Management's willingness to involve works councils in the further training process depends on the technological equipment (Rego, 2021). Staples and Whittall (2021) remark that the traditional co-determination habitus of works councils, which is reactive and defensive, makes them reluctant to 'move with the times' and fear of ICT remains. Since members of the works council might have no in-depth expertise of the required skills to support workers efficiently, new technologies could impose a threat to works councils.…”
Section: Firms' Digital Equipmentmentioning
confidence: 99%
“…The Covid‐19 pandemic has shown that more remote work could make within‐firm communication more difficult (Yang et al., 2022). Staples and Whittall (2021) find that works councils still put a high emphasis on analogue face‐to‐face interactions with the workforce. Therefore, more remote work in firms above the industry level of technology could make communication between the works councils and employees more difficult.…”
Section: Link Between Work Councils and Further Trainingmentioning
confidence: 99%